Lipid Class Composition and Heparin Sensitivity in the Activated Partial Thromboplastin Time - Stevenson, K J; Easton, Ann C; Thomson, Jean M; Poller, L (Thrombosis and Haemostasis, 1983)
In an APTT reagent, prepared from purified lipids, the role of phosphatidyl serine (PS) in determining the sensitivity of the APTT test system to measurement of the effect of heparin in plasma has been evaluated. As the concentration of PS decreases sensitivity to heparin increases but procoagulant activity decreases. Dilution of the test liposome over a wide range (1 g/1 to 30 mg/1) had a minimal effect on the clotting time. At levels below 30 mg/1, however, the amount of total lipid appeared to be rate limiting; a loss of procoagulant activity being paralleled by an increase in heparin sensitivity. Phosphatidyl inositol (PI) was not a satisfactory substitute for PS in the APTT method studied. The degree of unsaturation of test liposomes appeared to have no effect on either procoagulant activity or sensitivity to heparin at the lipid concentration employed.In the light of these findings, a more critical appraisal of the phospholipid components of APTT reagents should facilitate the development of more reliable reagents for heparin control. A further benefit of this type of approach should be a reduction in the acknowledged wide variations in sensitivity to heparin which exist between available APTT reagents.
Keywords: Activated partial thromboplastin time; Heparin; Phosphatidyl serine